2021
DOI: 10.1002/dmrr.3489
|View full text |Cite
|
Sign up to set email alerts
|

Serum creatinine levels and risk of nonalcohol fatty liver disease in a middle‐aged and older Chinese population: A cross‐sectional analysis

Abstract: Background: Non-alcoholic fatty liver disease (NAFLD) is now regarded as the hepatic manifestation of metabolic syndrome (MetS). Recent research has suggested that serum creatinine (SCr) may be an indicator of MetS and its related diseases. We aimed to investigate the association between SCr and NAFLD in Chinese adults. Methods: A cross-sectional sample of 8862 subjects aged 40 years or older (40-73 years) from China were analysed in this study. The anthropometric measurements, laboratory tests, and hepatic ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…In the general US population, liver fibrosis assessed using vibration controlled transient elastography (VCTE) is associated with CKD, specifically with a proteinuric phenotype, but not with traditional risk factors[ 25 ]. A study based on 8862 subjects reported that SCr levels were independently associated with HS [ 26 ]. Elevated SCr levels, even within the normal range, were associated with a higher risk of NAFLD [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the general US population, liver fibrosis assessed using vibration controlled transient elastography (VCTE) is associated with CKD, specifically with a proteinuric phenotype, but not with traditional risk factors[ 25 ]. A study based on 8862 subjects reported that SCr levels were independently associated with HS [ 26 ]. Elevated SCr levels, even within the normal range, were associated with a higher risk of NAFLD [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study based on 8862 subjects reported that SCr levels were independently associated with HS [ 26 ]. Elevated SCr levels, even within the normal range, were associated with a higher risk of NAFLD [ 26 ]. Similarly, the current study demonstrates for the first time that elevated SCr levels are an independent risk factor for HS, and logistic regression analysis after adjusting for confounding factors suggests that SCr has a direct effect on HS.…”
Section: Discussionmentioning
confidence: 99%
“…Current evidence showed that creatinine could be a critical index of model for end-stage liver disease (MELD) and hepatorenal syndrome (HRS) to assess liver disease severity and mortality risk (Kamath et al, 2001;Belcher et al, 2015). A cross-sectional analysis also revealed that NAFLD subjects have higher serum creatinine than those without NAFLD (Niu et al, 2021). Elevated serum uric acid-to-creatinine ratio (SUA/ Cr) may be a reliable marker for predicting NAFLD (Seo and Han, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Diabetic patients have lower seropositivity rate of COVID-19 vaccination than healthy population [ 20 ]. Serum creatinine level is an useful indicator of metabolic syndrome in HS patients [ 21 ]. Renal impairment was defined as creatinine level >106 μmol/L for male and >97 μmol/L for female [ 22 ].…”
Section: Methodsmentioning
confidence: 99%